2018
DOI: 10.3389/fncel.2018.00250
|View full text |Cite
|
Sign up to set email alerts
|

Sodium–Calcium Exchanger Can Account for Regenerative Ca2+ Entry in Thin Astrocyte Processes

Abstract: Calcium transients in thin astrocytic processes can be important in synaptic plasticity, but their mechanism is not completely understood. Clearance of synaptic glutamate leads to increase in astrocytic sodium. This can electrochemically favor the reverse mode of the Na/Ca-exchanger (NCX) and allow calcium into the cell, accounting for activity-dependent calcium transients in perisynaptic astrocytic processes. However, cytosolic sodium and calcium are also allosteric regulators of the NCX, thus adding kinetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
0
20
0
3
Order By: Relevance
“…8). The transport direction of NCX, however, can reverse in response to increases in intracellular sodium and calcium concentrations, thereby mediating calcium import Fern et al, 2014;Boddum et al, 2016;Boscia et al, 2016;Parpura et al, 2016;Brazhe et al, 2018;Gerkau et al, 2018).…”
Section: Reverse Ncx Contributes To Local Calcium Signaling In Neocormentioning
confidence: 99%
“…8). The transport direction of NCX, however, can reverse in response to increases in intracellular sodium and calcium concentrations, thereby mediating calcium import Fern et al, 2014;Boddum et al, 2016;Boscia et al, 2016;Parpura et al, 2016;Brazhe et al, 2018;Gerkau et al, 2018).…”
Section: Reverse Ncx Contributes To Local Calcium Signaling In Neocormentioning
confidence: 99%
“…Such sparks may not be detectable in our experimental conditions (resolution and speed of imaging) but still could play a role in astrocyte physiology, for example, trigger local release of gliotransmitters. A recent computational study has also suggested that local Ca 2+ sparks can be amplified through NCX (Brazhe et al, ). Moreover, Ca 2+ sparks in ER/mitochondria‐free leaflets can potentially integrate to trigger spreading Ca 2+ events in their parent astrocytic branches containing the Ca 2+ stores.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Ca 2+ entry through the VGCCs may still need to be amplified by CICR (Carmignoto, Pasti, & Pozzan, 1998). Na + /Ca 2+ exchanger (NCX) can transport Ca 2+ into the astrocytes upon increase in intracellular Na + concentration which occurs during glutamate uptake (Brazhe, Verisokin, Verveyko, & Postnov, 2018;Oschmann, Mergenthaler, Jungnickel, & Obermayer, 2017;Rojas et al, 2007). Other sources of the Ca 2+ entry in astrocytes include store-operated channels ORAI1 and transient receptor potential type A channels (TRPAs) (Bazargani & Attwell, 2016;Shigetomi, Jackson-Weaver, Huckstepp, O'Dell, & Khakh, 2013).…”
mentioning
confidence: 99%
“…NCX usually works in a forward mode, extruding Ca 2+ and transporting Na + into the cell. When intracellular Na + concentration increases, NCX extrudes Na + and brings Ca 2+ in Brazhe et al (2018) and Wade et al (2019). Several mechanisms are reported to increase intracellular Na + concentration in astrocytes.…”
Section: Source Of Calcium In Astrocytesmentioning
confidence: 99%